2011
DOI: 10.1039/c0nr00980f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of ceria nanorods and nanochains; the effect of dislocations, grain-boundaries and oriented attachment

Abstract: We predict that the presence of extended defects can reduce the mechanical strength of a ceria nanorod by 70%. Conversely, the pristine material can deform near its theoretical strength limit. Specifically, atomistic models of ceria nanorods have been generated with full microstructure, including: growth direction, morphology, surface roughening (steps, edges, corners), point defects, dislocations and grain-boundaries. The models were then used to calculate the mechanical strength as a function of microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 52 publications
(54 reference statements)
1
37
0
Order By: Relevance
“…2(c) and 2(d)). Thus, a phase transition from a fluorite CeO 2 crystal structure is observed, which is in good agreement with the classical molecular dynamics simulation reported by Sayle et al 45 However, there are large differences between the calculated and experimental fracture strengths. A fracture strength of 22.7 GPa is obtained from the DFT calculation, whereas the experimental value is 0.250 GPa.…”
Section: Resultssupporting
confidence: 80%
“…2(c) and 2(d)). Thus, a phase transition from a fluorite CeO 2 crystal structure is observed, which is in good agreement with the classical molecular dynamics simulation reported by Sayle et al 45 However, there are large differences between the calculated and experimental fracture strengths. A fracture strength of 22.7 GPa is obtained from the DFT calculation, whereas the experimental value is 0.250 GPa.…”
Section: Resultssupporting
confidence: 80%
“…Figure 4a shows the clear lattice fringes of {111} and {200} with interplanar spacings of 0.31 nm and 0.28 nm, indicating the cubic structure of CeO 2 nanorods with [211] growth direction. Although there is only one study reporting the synthesis of ceria nanorods with the same growth direction, 49 the feasibility of producing CeO 2 nanorods oriented along [211] was recently confirmed by Sayle et al 50 using atomistic simulation. By conducting detailed morphological analysis for nanorods formed at the early stage, Du et al 49 also successfully demonstrated that CeO 2 nanorods with the [211] orientation were grown by the so-called “oriented attachment” mechanism, in which adjacent nanoparticles are self-assembled by sharing a common crystallographic orientation followed by joining these particles at a planar interface, eventually leading to the development of single crystalline anisotropic structure.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a Σ3 grain boundary evolved within the 6 nm polyhedral nanoparticles, whereas a Σ11 grain boundary evolved in the 8 nm particle Previously, nanorods with Σ3 grain boundaries were calculated to have a compressive yield strength of 10 GPa. 38 Here, we find that 6 nm NP comprising Σ3 grain boundaries have an identical (10 GPa) compressive yield strength, which suggest that the shape is less important than the microstructure. Indeed, the 8 nm NP, which includes a Σ11 grain boundary, has a compressive strength of only 6 GPa.…”
Section: ■ Discussionmentioning
confidence: 91%